Music schools as forerunners towards collaborative professionalism - Westerlund, Heidi; Hahn, Michaela; Björk, Cecilia (Routledge, 2024)
This chapter raises fundamental questions about the role of collaboration in instrumental and vocal music education in a rapidly changing society. Given public demands for free access, equity, and wide participation as well as the societal responsibility of music education understood as a service to communities, what music schools may be expected to offer includes, but also reaches beyond traditional musical expertise. Researchers now largely agree that teams, communities of practice, and networks can serve as locations for learning and enhancing professional practice and as locations for novelty and innovation. The authors suggest that a shift towards collaborative professionalism in music education may enable music schools to respond to wider societal concerns and act as game changers in processes of making contemporary societies not just musically better but also better and more sustainable places to live. The chapter sets the stage for theoretical and practical understandings of the potential that collaborative professionalism holds for what counts as excellent work in twenty-first-century instrumental and vocal education.
Keywords: musiikki; musiikkikasvatus; musiikkioppilaitokset